A PRACTICAL GUIDE TO SOCIAL EDUCATION FOR TEACHERS AND EDUCATORS - Dedy Ari Nugroho; Ismaul Fitroh; Suhana Sarkawi (Adisam Publisher, 2025)
This practical guide aims to equip teachers and educators with effective strategies in teaching social education, which is an essential element in the development of students' life skills. The main focus of the guide is on instilling social values such as empathy, co- operation and responsibility, which are vital for positive participation in society. Inclusive and adaptive learning methods are emphasised to accommodate the diverse needs of students, through techniques such as project-based learning and group activities. In addition, the guide highlights the utilisation of technology as a tool to improve access and interactivity of learning, and to introduce a global perspective on social issues. With this holistic approach, the guide aims to create a supportive and collaborative learning environment that supports students' social and emotional development.